Genetic variation associated with thyroid autoimmunity shapes the systemic immune response to PD-1 checkpoint blockade - Zia Khan (Nature Portfolio, 2021)
Endocrinopathies, such as thyroid autoimmunity, are common among patients treated with immune checkpoint inhibitors. Here, by using a polygenic risk score (PRS) derived from a hypothyroidism GWAS, the authors show that cancer patients with high PRS are at increased risk of atezolizumab (anti-PD-L1)-induced thyroid dysfunction, a condition associated with systemic response to PD-1 checkpoint blockade and longer overall survival.